Relationships between students' psychological factors and science performance among Iranian students - Shahranavard, Maryam (2012)
Numerous studies have been conducted on the relation between students’psychological factors and performance outcomes. Yet, no study investigated selfconcept, self-efficacy, self-esteem and anxiety in science performance,simultaneously. Therefore, the main objective of the present study is to investigate relationship between self-concept, self-efficacy, self-esteem, anxiety, and science performance among Eighth Grade Iranian students with some demographic variables such as gender, geographical location and socio-economic status. Six hundred and eighty Iranian eighth grade students were randomly selected out of twenty three schools. Five valid and reliable instruments were used to assess Self-concept Attribute Attitude Scale (SaaS), State-Trait Anxiety Inventory (STAI), Coopersmith Self-Esteem Inventory (CSEI), General Self-Efficacy scale (GSE), and Science Self-Efficacy Questionnaire (SSEQ). Both descriptive and inferential statistics were used to analyze the data in the study using SPSS 18. The statistical techniques used were Descriptive Statistics, ANOVA, MANOVA, Multiple Regression Analysis, Pearson Correlation, and hierarchical Regression Analysis. The results of ANOVA showed that there is no significant difference between male and female students in science performance, while, there is a significant difference between urban and suburban in science performance, and there is significant difference between low and high family’s income .groups in science performance.The results of MANOVA revealed that there were significant differences in the other variables between male and female groups except self-concept. Whereas, there were significant difference between groups (urban, suburban, rural areas) in science self-efficacy only. There were significant difference between groups (high, medium, low family’s income) in science anxiety, self-esteem and self-efficacy. The results of multiple regression analysis showed that science self-concept and self-concept were statistically significant in science performance. The results of hierarchical regression analysis showed that gender did not moderate the relationship between predictor variables (science self-concept, self-concept, science anxiety, anxiety, self-esteem, self-efficacy, and science self-efficacy) and students’ science score. Therefore, based on the results of the findings mentioned, it is vital that the psychological theories about self-concept and science self-concept in science teaching were used. Hence, applying the knowledge and theories taught in Educational Psychology is important for teachers to know about their students’ abilities. Consequently, it is important to focus on students’ achievement and selfconcept and science self-concept in guidance school education.